GE_GERICHTE P/11923/2016 vom 21. April 2020 - GE Cour de justice (2020)
DISPOSITIONS PÉNALES DE LA LCR;CONDUITE MALGRÉ UNE INCAPACITÉ;IVRESSE;IRRESPONSABILITÉ;ÂGE;CONCOURS D'INFRACTIONS | LCR.91.al2; CPP.371.al1; CPP.366.al4; CPP.87.al1; CPP.199; CPP.202.al2; CPP.88; LCR.90.al2; LCR.26.al1; LCR.31.al1; LCR.27.al1; LCR.91a; CP.19; CP.49